2008
DOI: 10.1167/iovs.07-0419
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Disruption of Barrier Function in Cultured Human Corneal Epithelial Cells Induced by Tumor Necrosis Factor-α in a Manner Dependent on NF-κB

Abstract: TNF-alpha disrupted the barrier function of HCE cells, apparently by affecting the localization of ZO-1 at TJs in a manner dependent on NF-kappaB at late phase. This action of TNF-alpha may contribute to the loss of corneal epithelial barrier function associated with ocular inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 57 publications
3
61
0
1
Order By: Relevance
“…There may be evidence to support the proposition that corneal epithelial barrier function could be compromised by higher levels of shear stress in the Asian eye. For example, mechanical insult to the cornea induced by shear stress may be responsible for epithelial cell apoptosis, desquamation, and disruption of tight junctions [35][36][37][38][39] and has been implicated as a contributing factor to the inflammatory response associated with dry eye [40,41], these factors are likely responsible for increased corneal epithelial permeability. Shear stress-induced epithelial surface disruption and inflammation could explain recent studies reporting greater prevalence of dry eye in Asians compared with non-Asians [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…There may be evidence to support the proposition that corneal epithelial barrier function could be compromised by higher levels of shear stress in the Asian eye. For example, mechanical insult to the cornea induced by shear stress may be responsible for epithelial cell apoptosis, desquamation, and disruption of tight junctions [35][36][37][38][39] and has been implicated as a contributing factor to the inflammatory response associated with dry eye [40,41], these factors are likely responsible for increased corneal epithelial permeability. Shear stress-induced epithelial surface disruption and inflammation could explain recent studies reporting greater prevalence of dry eye in Asians compared with non-Asians [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Ma and co-workers have shown that the TNFa-induced increase in TJ permeability of Caco-2 cells was associated with a downregulation of ZO-1 protein expression, which was accompanied by an altered tight junction localization of ZO-1, and this was prevented by NFkB inhibitors (Ma et al, 2004). In corneal epithelial cells, TNFa disrupted the barrier function of HCE cells, with a disappearance of ZO-1 at TJs resulting in a decrease of R t , whereas the NFkB inhibitor curcumin blocked these effects of TNFa on R t and the subcellular localization of ZO-1 (Soler et al, 1999;Kimura et al, 2008). It has been hypothesized that the activation of NFkB can induce transcription and translation of certain target genes, which subsequently lead to the inhibition of TJ protein expression.…”
Section: Fig 6 Specific Blockers In Tnfa-and Berberine-induced Tj Rmentioning
confidence: 99%
“…22,23 Furthermore, another in vitro study using the NF-B inhibitor curcumin indicated that barrier function and subcellular localization of zona occludens (ZO)-1 is dependent on NF-B following TNF-␣ administration. 24 Interestingly, results in epithelial-specific IKK knockout mice showed that colitis-induced cell proliferation was unaffected while crypt cell apoptosis increased in the absence of NF-B signaling. 25 These studies highlight the importance of using site-specific models of NF-B-deficient signaling to understand NF-B biology in the intestine.…”
mentioning
confidence: 99%